PREVENTIVE MAINTENANCE OF BREAKER MACHINE TO PREVENT DAMAGE AND IMPROVE DURABILITY AT PT. BUKIT ANGKASA MAKMUR (BAM) CENTRAL BENGKULU REGENCY - puspawan angky; Zuliantoni; Ahmad Rifki Abipraya (UNIB Press, 2026)
This research was conducted at PT. Bukit Angkasa Makmur, a company engaged in the processing of natural rubber into crumb rubber. The research focus of this activity is the implementation of preventive maintenance on the breaker machine, which is used in the initial stage of rubber processing. Common issues such as bearing wear, dull rotor and stationary blades, and v-belt damage often result in operational disruptions. Therefore, an analysis and scheduled implementation of preventive maintenance was conducted monthly during the third and fourth weeks from October to December 2024. The observations showed that preventive maintenance significantly improved machine reliability, extended service life, and reduced repair costs. With well-planned maintenance, the company can ensure smoother production processes and greater operational efficiency.